2004
DOI: 10.1074/jbc.m312693200
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Contain a Non-proteinaceous Pool of Copper in the Mitochondrial Matrix

Abstract: The yeast mitochondrion is shown to contain a pool of copper that is distinct from that associated with the two known mitochondrial cuproenzymes, superoxide dismutase (Sod1) and cytochrome c oxidase (CcO) and the copper-binding CcO assembly proteins Cox11, Cox17, and Sco1. Only a small fraction of mitochondrial copper is associated with these cuproproteins. The bulk of the remainder is localized within the matrix as a soluble, anionic, low molecular weight complex. The identity of the matrix copper ligand is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
205
1
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 60 publications
3
205
1
2
Order By: Relevance
“…Recent data indicate that Cox17 tethered to the inner mitochondrial membrane is fully functional, however (15). In addition, mitochondrial copper levels are independent of the presence of Cox17 (16). These results suggest that trafficking copper ions between the cytosol and the mitochondrial intermembrane space is not a function of Cox17.…”
supporting
confidence: 49%
“…Recent data indicate that Cox17 tethered to the inner mitochondrial membrane is fully functional, however (15). In addition, mitochondrial copper levels are independent of the presence of Cox17 (16). These results suggest that trafficking copper ions between the cytosol and the mitochondrial intermembrane space is not a function of Cox17.…”
supporting
confidence: 49%
“…In yeast and mouse liver 85 and ~70% of the total mitochondrial copper is associated with this matrix CuL complex. Although the identity of the ligand remains unresolved, the matrix CuL pool is accessible to a heterologous cuproenzyme (Cobine et al 2004). The mechanism by which Aft1 (and Aft2) sense cellular iron levels involves the mitochondrion (Chen et al 2004;Chen et al 2002).…”
Section: Metal Ion Pools Within Mitochondriamentioning
confidence: 99%
“…However, the increased copper concentration is not likely to be working by providing copper to Cu/Zn SOD, since copper greatly increased the life span of an SOD1 mutant. It has been demonstrated that yeast contain a pool of copper in the mitochondrial matrix that is not associated with any protein (Cobine et al, 2004). This pool may be used to buffer copper concentration in the cell, or to provide copper to cytochrome c oxidase and the fraction of Cu/ZnSOD present in the intermembrane space (Sturtz et al, 2001).…”
Section: Discussionmentioning
confidence: 99%